Investigation of gypsum composites with different lightweight fillers. (23rd August 2021) - Doleželová, Magdaléna; Scheinherrová, Lenka; Krejsová, Jitka; Keppert, Martin; Černý, Robert; Vimmrová, Alena
Highlights: Gypsum composites with different lightweight fillers were investigated. Structure of gypsum matrix is influenced by the filler porosity. Gypsum crystals are smaller and more dense packed around porous particles. Composite with expanded clay aggregates has highest strength. Composite with PUR foam is most favourable from environmental point of view. Abstract: Structure and behaviour of gypsum composites, prepared from flue gas desulfurization binder and three types of fine fillers (silica sand, perlite, expanded clay aggregate and waste polyurethane foam) were studied. Their structure and composition were investigated by SEM, XRD and porosimetry, mechanical, thermal and moisture properties were tested. It was found that the type and surface quality of the aggregates affect the shape and size of gypsum crystals significantly. Largest gypsum crystals are formed in the mortars with non-porous particles. With increasing surface roughness of particles the strength of the mortars increases. Mortar with expanded clay filler has the highest strength, its compressive strength was comparable with the compressive strength of the reference material with silica sand, but its bulk density was more than 40% lower and its thermal conductivity decreased to 20% of the thermal conductivity of reference material. The mortar with waste polyurethane foam has the lowest strength (2.9 MPa at 7 days) but best thermal conductivity (0.211 W/m.K) of all materials. Technical properties of composite with waste polyurethane are still sufficient for building purposes and its environmental impact is lowest of all materials.